Dispensasi Nikah Dalam Penetapan No. 1234/Pdt.P/2020/Pa.Pra Ditinjau Dari UU No. 16 Tahun 2019 Tentang Perubahan Atas UU No. 1 Tahun 1974 Tentang Perkawinan - Siska Wilia Sapitri; Aris Munandar; Lalu Hadi Adha (Fakultas Hukum Universitas Mataram, 2023)
This research’ aim was to analyses judge’s consideration on marital dispensation as accommodated in the Determination Number 1234/Pdt.P/2020/PA.Pra viewed from the perspective of Law Number 16 of 2019 on the Amendment of Law Number 1 of 1974 on Marriage and to analyze what is the “urgent reason” in the determination. This research applied normative juridical approach. Result of the study shows that in principle judge’s consideration if the child applicant was not married will cause negative impact in the future. This urgent reason as judge’s consideration are: readiness to settle down, have established long-standing relationships, and have the ability to do so.